Capabilities of developing (archaeological, historical and religious tourism) in Kfri - Salim, Gharib Ali; Rashid, Prof.Dr.Shirwan Omar (Sulaimani Journal for Humanities, 2026)
This research entitled development capabilities (archaeological, historical and religious tourism) in Kufri aims to show the archaeological, historical and religious tourism capabilities and how to develop in the city, which is one of the important principles of tourism development It has not been used to attract tourists and revive the city's economy, due to lack of services and backward infrastructure. To achieve the goal of the research, we used both methods (descriptive and principled) and with geographical information systems, the research finally reached a number of conclusions, including the city of Kufri contains many historical and religious remains Therefore, we recommend that attention be paid to tourism in general and archaeological and religious historical tourism in particular, because the city is rich in many archaeological sites through which tourism activities can be developed and economically beneficial for the residents of the city.
Keywords: Tourism; Development; Religious and Historical Monuments; Kfri